1988
DOI: 10.3758/bf03333115
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrollable shock, forebrain norepinephrine, and stimulus selection during choice-escape learning

Abstract: Exposure to uncontrollable shock impairs later choice-escape learning in rats. A deficit occurs only when an irrelevant cue is presented on choice trials and the rat is unable to ignore the cue. Three experiments examined the role of stress-induced depletion of forebrain norepinephrine (NE) in the choice-accuracy deficit. Experiments 1 and 2 established a relationship between stressfulness of pretreatment sessions, magnitude of the deficit in later choice escape, and depletion of forebrain NE upon reexposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…Similar percentages in explained variance were obtained in Experiments 1 and 2 with the shuttle-escape measure (54%) and saccharin finickiness (48%). These data confirm and extend the finding that pretreatment stressor severity is a critical extrinsic modulator of distress and helplessness (Anisman & Zacharko, 1986; Looney & Cohen, 1972; Minor, Pelleymounter, & Maier, 1988). At the same time, however, the experimental variable does not explain about 50% of the variance in these test measures.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar percentages in explained variance were obtained in Experiments 1 and 2 with the shuttle-escape measure (54%) and saccharin finickiness (48%). These data confirm and extend the finding that pretreatment stressor severity is a critical extrinsic modulator of distress and helplessness (Anisman & Zacharko, 1986; Looney & Cohen, 1972; Minor, Pelleymounter, & Maier, 1988). At the same time, however, the experimental variable does not explain about 50% of the variance in these test measures.…”
Section: Discussionsupporting
confidence: 87%
“…Escape latency increased across preshock conditions to a point at which most individuals in the 120-shock group showed severe impairment of escape performance. This substantial effect concurs with findings from related studies on stressor severity (Anisman & Zacharko, 1986; Looney & Cohen, 1972; Minor, Pelleymounter, & Maier, 1988). Nonetheless, only 49% of the variance in escape latencies was accounted for by the number of preshocks.…”
Section: Analysis Of Intrinsic Variancesupporting
confidence: 91%
“…Previous research has shown that comparatively mild stressors provoke excessive neural activation in several transmitter systems and brain regions in rats preexposed to inescapable shock 24 hr earlier (Anisman & Zacharko, 1986;Minor, Pelleymounter, & Maier, 1988; J. M. Weiss et al, 1981). This reaction to test stimuli resembles the conditions under which adenosine is liberated into the extracellular space as a compensatory reaction to rapid energy expenditure produced by excessive neural excitation (Ames, Li, Heher, & Kimble, 1992;Fredholm & Dunwiddie, 1988;Rail, 1990;Meghji, 1991;Newby, 1984;Stone & Bartrup, 1991).…”
Section: Discussionmentioning
confidence: 95%
“…Pavlovian cues may modulate the chronicity of the arousal in these systems during pretreatment. Moreover, reexposure to Pavlovian fear cues during testing could rapidly reactivate these already taxed neural systems (e.g., Minor, Pelleymounter, & Maier, 1988; Weiss & Simson, 1985). The long-term effect of chronic activation of these neural substrates during pretreatment and testing could result in the neural chemical changes that are frequently observed in inescapably shocked subjects (e.g., Anisman & Sklar, 1979; Hallhammer, Bell, Ludwig, & Rea, 1983; Weiss et al, 1981).…”
Section: Discussionmentioning
confidence: 99%